Synthesis and characterization of core‐shell magnetic molecularly imprinted polymers for selective extraction of allocryptopine from the wastewater of Macleaya cordata (Willd) R. Br. Issue 8 (26th March 2020) - Wang, Lu; Wang, Yanhong; Zhou, Binbin; Zhong, Ming
Abstract: A novel type of magnetic molecularly imprinted polymers (MMIP) as the solid‐phase extraction sorbent was prepared, which can extract effectively the allocryptopine from the waster of Macleaya cordata (Willd) R . Br . In this study, MMIP was synthesized by using Fe3 O4 @SiO2, 4‐vinyl‐pyridine, ethylene glycol dimethacrylate, and allocryptopine, and these ingredients worked as magnetic core, functional monomer, cross‐linker, and template, respectively. Concluded by the calculation of Gaussian 09 software, different ratio models of 4‐vinyl‐pyridine and allocryptopine were simulated, and the optimal ratio was 1:5 and the energy was −2205.34 kJ/mol. Transmission electron microscopy, vibration sample magnetometry, X‐ray diffraction, Fourier transform infrared spectroscopy, and thermogravimetric analysis were used to determine the morphology and structure of MMIP. Furthermore, the results of adsorption experiments indicated that MMIP had high selectivity, excellent recyclability, and good adsorption performance (9.86 mg/g, 298 K). The adsorption process was consistent with the Langmuir adsorption isotherm ( R 2 > 0.98, 298 K) and pseudo‐second‐order kinetics model ( R 2 > 0.99, 298 K). After six times adsorption‐desorption experiments, the adsorption amount of MMIP only reduced to 8.5%. In the experiments of selective adsorption, MMIP has better adsorption properties for allocryptopine (ALL, C21 H23 NO5 ) than those having the same functional group. The limit of detection (LOD) was 0.4 μg/mL. The relative standard deviation ranged from 0.09% to 0.72%. The recovery of allocryptopine in samples ranged from 93.60% to 106.19%. In addition, the synthesized complex had a certain adsorption effect on allocryptopine separating from the wastewater of Macleaya cordata (Willd) R . Br .